(untitled) (REMUNOM, 2024)
The use of playful activities, used as a didactic methodological resource in education, motivates and arouses the student’s interest, contributing to more attractive and meaningful learning, allowing the retention of aborted content in the classroom. The research aimed to use the Domino game of operations with natural numbers in order to assist the teaching-learning process in the classroom in the development of mental calculation and use of the concepts of addition, subtraction, multiplication and division in problem solving. with students in the 6th year of elementary school. The game was held during normal class hours in the morning, with a total duration of 2 classes of 50 minutes each, with the participation of 40 students from the 6th year of Elementary School, in a public school located in the city of Pium–TO. 10 (ten) groups were formed (4 students per group) to present and explain the rules of the game. After using the game, students were invited to answer a questionnaire with the following closed questions. Through the analysis of the application of the game, it was observed that the playful approach carried out presented values ​​equal to or greater than 70% in all questions questioned, demonstrating good acceptance and contributing to significant learning about the content studied. The game provided a socialization situation, a relaxed and interactive environment for contextualized learning that was closer to the student’s daily life. Therefore, the domino of operations with natural numbers was an auxiliary strategy of great relevance for learning and maintaining the study of basic operations, supporting the teacher to contextualize the content and motivate students.